Three Cases of Pigmentary Incontinence and Literature Review - Yunfeng Zhang; Yuan Wang; Jinpu Zhang; Na Song (Journal of Pediatrics Review)
Background: Incontinentia pigmenti (IP) is a rare X-linked dominantly inherited genetic skin disorder in which most male infants cannot survive. The clinical manifestation is mainly characterized by a characteristic rash, which may also involve multiple extracutaneous organs. Case Presentation: We reported three children with pigmentary incontinence, and a literature review was conducted to elaborate on the clinical manifestations of various systems in patients with IP. Conclusions: IP is a disease that involves multiple systems and patients with IP are likely to develop serious ocular and neurologic complications. Once diagnosed, neurologists, ophthalmologists, and dentists must consult and evaluate patients multidisciplinaryly. Early intervention and adherence to lifelong follow-up are needed.